Improving Water Saving Behaviors: The Role of STEM-EDP Education for Future Physics Teachers - Alam, Muhammad Ikhsan Bachrul; Sulaeman, Nurul Fitriyah; Nuryadin, Atin; Saeki, Hideya (Program Studi Pendidikan Fisika, 2025)
In a global context, water quality issues have become a major environmental issue affecting many countries, including Indonesia, especially in the East Kalimantan region. This research aims to determine the difference and increase in water saving behavior (WSB) of pre-service physics teachers after involved in learning with the Science - Technology - Engineering - Mathematics (STEM) - Engineering Design Process (EDP) model. The research method used was pre-experimental research using a one-group pretest-posttest design with a quantitative approach. The sampling technique in this research was purposive sampling, involving 31 pre-service physics teachers. A questionnaire that had been adapted from previous research was used as an instrument in this research. The learning was carried out by giving 4 STEM-EDP worksheets with a total of 6 offline meetings. The results showed that there was a difference and increase in WSB after learning with the STEM-EDP with moderate criteria overall. The results of this research indicate that the STEM-EDP learning model may improve positive behavior toward the environment.